DIFFERENTIAL DENSITY OF PERMANENT TEETH DEVELOPMENT USING PANORAMIC RADIOGRAPH WITH IMAGE-J ANALYSIS IN CHILDREN AGED 6-9 YEARS FEEDED EXCLUSIVELY BREAST MILK AND FORMULA MILK - Moh. Yusuf; Kusuma Arbianti; Shella Indri Noviani; Ristiwi Suhertam (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: Digital panaromic radiograph is used to assist dentist in taking complete pictures of the oral cavity. ImageJ is a software application that helps assess the enamel density of permanent teeth. The density of permanent teeth enamel is influenced by many factors, including the consumption of milk given since infancy. Exclusive breastfeeding has a more complete content and rich of benefit than formula milk. The aim of this study is to determine the enamel density of permanent teeth by using a panaromic radiograph technique with ImageJ application to children aged 6-9 years who were given exclusive breastfeeding and formula milk.Method: This is an analytic observational study using a retrospective cohort approach. The sampling technique used consecutive sampling and obtained 23 respondents with panaromic radiographs of children aged 6-9 years consisting of 10 children consuming formula milk and 13 children consumingexclusive breastfeeding. The enamel density was assessed using ImageJ application. The data was analyzed statistically using Man-Whitney comparative testResult: The results reveal that there was difference in the permanent teeth enamel density between children aged 6-9 years who consumed exclusive breastfeeding and formula milk which showed p value of 0,021.Conclusion: The conclusion of this study is that the type of milk has an effect on the enamel density of permanent teeth and children who consume exclusive breastfeed milk have a higher permanent teeth enamel density